2010
DOI: 10.1051/ject/201042045
|View full text |Cite
|
Sign up to set email alerts
|

The Perfusionist’s Role in a Collaborative Multidisciplinary Approach to Blood Transfusion Reduction in Cardiac Surgery

Abstract: Red blood cell transfusion is associated with adverse outcomes. Transfusion practices remain varied in cardiac surgery and are a subject of growing debate. We initiated a data-driven, multidisciplinary effort to decrease allogeneic red blood cell transfusion at our institution. Creative perfusion strategies are an essential component of our program and led to a low transfusion rate. Innovations in treatment protocols were implemented and evaluated to reduce hemodilution associated with the cardiopulmonary bypa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Their retrospective study of 2979 consecutive cardiac surgical patients showed a reduction in red cell transfusions from 43-13.6% for all patients and 38.5-8.7% for coronary artery bypass patients. The authors noted that their first step was to achieve standardization among the perfusion team for a successful blood conservation program (15).…”
mentioning
confidence: 99%
“…Their retrospective study of 2979 consecutive cardiac surgical patients showed a reduction in red cell transfusions from 43-13.6% for all patients and 38.5-8.7% for coronary artery bypass patients. The authors noted that their first step was to achieve standardization among the perfusion team for a successful blood conservation program (15).…”
mentioning
confidence: 99%